Особливості політичного конфлікту в трансформаційних умовах: на прикладі України - Завгородня, Юлія Володимирівна; Завгородня, Ю. В.; Завгородняя, Юлия Владимировна; Zavhorodnia, Yuliia V. (Одеса: Фенікс, 2018)
Сучасна українська держава позиціонує себе, як незалежна, соціальна, правова та демократична країна. Нормативно правові акти визначають демократичний політичний режим у суспільстві, однак об’єктивні чинники та факти показують певну невідповідність цього постулату тим політико-правовим процесам, які відбуваються у суспільстві. А тому, все частіше науковці характеризують Україну, як країну, яка перебуває у перехідній площині в напрямку зміни політичного режиму. Усі зміни, які відбуваються в країні супроводжуються політичними конфліктами. Все частіше вони набувають деструктивного прояву, та потребують відшукання дієвого механізму їх вирішення. Аналіз причин виникнення політичних конфліктів допоможе швидко реагувати на них та врегульовувати.

Современное украинское государство позиционирует себя как независимое, социальное, правовое и демократическое государство. Нормативно-правовые акты определяют демократический политический режим в обществе, однако объективные факторы и факты показывают определенное несоответствие этого постулата тем политико-правовым процессам, которые происходят в обществе. А потому, все чаще ученые характеризуют Украину как страну, которая находится в переходной плоскости в направлении изменения политического режима. Все изменения, которые происходят в стране сопровождаются политическими конфликтами. Все чаще они приобретают деструктивные проявления, и требуют отыскания действенного механизма их решения. Анализ причин возникновения политических конфликтов поможет быстро реагировать на них и регулировать.

The modern Ukrainian state positions itself as an independent, social, legal and democratic country. Normative legal acts define the democratic political regime in society, but objective factors and facts reveal some inconsistency of this postulate with the political and legal processes that take place in society. Therefore, scientists are increasingly characterizing Ukraine as a country that is in a transitional plane in the direction of changing the political regime. All changes taking place in the country are accompanied by political conflicts. They increasingly become destructive manifestations, and they need to find an effective mechanism for their solution. An analysis of the causes of political conflicts will help them respond quickly and resolve them. A transit society is confronted with a number of dangers and problems, such as conflict of interest, conflict of identity. On the example of a transitional society, it is possible to make certain analyzes and studies. The study of social and political changes provides a theoretical basis for finding effective practical mechanisms for solving problematic political issues that hinder positive political change. When researching the Ukrainian transit society, it is necessary to take into account all historical events and changes in the political elite. The authorities form the main directions of change. The problem of certain political changes is not the socially important value, but the benefit of certain political forces. Such circumstances are a brake element in solving national problems of Ukraine.
Завгородня Ю. В. Особливості політичного конфлікту в трансформаційних умовах: на прикладі України / Ю. В. Завгородня // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), А. В. Полухіна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2018. – Вип. 61. – С. 226-235.
Keywords: транзит; транзитне суспільство; політичний конфлікт; протиборство; демократичний режим; транзит; транзитное общество; политический конфликт; противоборство; демократический режим; transit; transit society; political conflict; confrontation; democratic regime; Research Subject Categories::LAW/JURISPRUDENCE